2006
DOI: 10.1086/505225
|View full text |Cite
|
Sign up to set email alerts
|

Immunization with Reverse‐Genetics–Produced H5N1 Influenza Vaccine Protects Ferrets against Homologous and Heterologous Challenge

Abstract: H5N1 vaccines may stimulate an immune response that is more cross-protective than what might be predicted by in vitro assays and, thus, hold potential for being stockpiled as "initial" pandemic vaccines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
102
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(108 citation statements)
references
References 38 publications
6
102
0
Order By: Relevance
“…Although it is possible that all four antigens are equally effective, further analysis with split vaccines (whole-virus preparations are inherently more immunogenic but also rarely used in humans in view of associated febrile responses), titrations of antigen dose, and more divergent challenge viruses are warranted and required to test the hypotheses that the ancestral antigens are more cross-reactive than some or all naturally occurring counterparts. Nevertheless, the ability of single antigens to protect across a range of challenge viruses is encouraging from the standpoint of vaccine stockpiling, as has been suggested by other ferret (22,23,6,24) and human studies (25). Although we observed no mortality or morbidity in H5N1 cross-clade ferret challenges, Govorkova et al (22) challenged HK213 (clade 1)-vaccinated animals with A/Hong Kong/156/97 (clade 0, 96% HA aa identity with the vaccine strain, excluding the cleavage peptide) and reported morbidity but no mortality.…”
Section: Discussionmentioning
confidence: 93%
“…Although it is possible that all four antigens are equally effective, further analysis with split vaccines (whole-virus preparations are inherently more immunogenic but also rarely used in humans in view of associated febrile responses), titrations of antigen dose, and more divergent challenge viruses are warranted and required to test the hypotheses that the ancestral antigens are more cross-reactive than some or all naturally occurring counterparts. Nevertheless, the ability of single antigens to protect across a range of challenge viruses is encouraging from the standpoint of vaccine stockpiling, as has been suggested by other ferret (22,23,6,24) and human studies (25). Although we observed no mortality or morbidity in H5N1 cross-clade ferret challenges, Govorkova et al (22) challenged HK213 (clade 1)-vaccinated animals with A/Hong Kong/156/97 (clade 0, 96% HA aa identity with the vaccine strain, excluding the cleavage peptide) and reported morbidity but no mortality.…”
Section: Discussionmentioning
confidence: 93%
“…For ferrets and monkeys, a positive control would need to be sought that is potentially highly pathogenic to humans. Indeed, highly pathogenic H5N1 strains have been shown to be neurovirulent in ferrets [4,5,12,23], whereas the recent novel, and less pathogenic, H1N1 virus is not [15]. To the best of our knowledge, there are no reports available of influenza viruses invading and replicating in the brain of monkeys, but if such a virus was available, it most likely would be highly pathogenic to humans.…”
Section: Discussionmentioning
confidence: 99%
“…Further, a single dose of a clade 1 H5N1 whole virus vaccine adjuvanted with incomplete Freund's adjuvant also fully protected mice against challenge with clade 1 virus at dosages of 7μg HA [32]. Recent studies with ferrets demonstrated that a 7 or 15μg dose of whole virus egg-derived vaccine (based on the clade 1 HK213 strain) protected against challenge with heterologous strains (clade 1 strains HK156 and VN1203) [33]. Using live, attenuated influenza H5N1 candidate vaccines broad cross-protection in mice and ferrets could be demonstrated.…”
Section: Discussionmentioning
confidence: 99%